Pseudospin-electron model at weak coupling - Stasyuk, I.V.; Mysakovych, T.S. (Condensed Matter Physics, 2002)
The static and dynamic dielectric susceptibility of the pseudospin-electron
model is investigated in the random phase approximation. The possibility
of the phase transition to the homogeneous phase, to the phase with doubly
modulated lattice period and to the incommensurate phase is revealed
in the regime µ = const depending on the value of the chemical potential.
The phase separation on the homogeneous and phase with doubly modulated
lattice period is established and the phase diagrams (n, h) are built.
The influence of the tunnelling-like splitting on the phase transition picture
is studied. The presence of pseudospin-wave excitations and the smooth
excitation spectrum and the possibility of their superimposing are revealed Досліджується статична та динамічна діелектрична сприйнятливість псевдоспін-електронної моделі в наближенні хаотичних фаз. В режимі Д = const виявлено можливість фазового переходу до однорідної фази, фази з подвійною модуляцією періоду ґратки та неспівмірної фази в залежності від значення хімічного потенціалу. Виявлено можливість фазового розшарування на однорідну фазу та фазу з подвоєнням ґраткового періоду та побудовано фазову діаграму (n,h) .Досліджено вплив тунельного розщеплення на фазові переходи. Встановлено присутність у системі псевдоспін-хвильових збуджень, неперервного спектру збуджень та можливость їх взаємоперекриття.